San Joaquin College of Law Moot Court Award's Dinner - Watkins, Howard::::::::: (1987)
Joby Dupuis passing out award certificate to Donna Tarter; Front row: Jan Pearson, Deloise Tritt, Todd Barsotti, and ?; Back far right: Charla D. Harbottle and James Harbottle